PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPEMIMPINAN TRANSAKSIONAL TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING PADA PT SINAR SOSRO TANJUNG MORAWA - Corry Magdalena (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2016)
Chairman of PT. Sinar Sosro Tanjung Morawa should maintain transactional leadership and transformational leadership as both can affect motivation and performance of employees. The study of transformational leadership is more positive effect of increasing motivation and performance but recall that effective leadership is a combination of both the leadership. The type of research is correlational study with the cross sectional. The sample in this research is 123 production employees of PT. Sinar Sosro Tanjung Morawa. This study uses path analysis Bayesian methods, with the independent variables of transformational leadership and transactional leadership, motivation and the dependent variable (Y1) and employee performance (Y2). The results showed that the Y1 equation, the coefficient of determination (R2) of its 11.5% influenced by variables transformational leadership and transactional leadership. As well as in the equation Y2, the coefficient of determination (R2) it is 24.3% influenced by transformational leadership, transactional leadership and motivation. In testing of Bayesian methods obtained in the equation Y1 which significantly affect motivation as an intervening variable is transformational leadership but transactional leadership has little effect (not significant). In the equation Y2 which significantly affect employees' performance is transformational leadership, but transactional leadership and motivation as an intervening variable has little effect (not significant).